2011
DOI: 10.1111/j.1464-5491.2011.03254.x
|View full text |Cite
|
Sign up to set email alerts
|

Temporal trends in diabetes prevalence and key diabetes risk factors in Scotland, 2003–2008

Abstract: These results suggest nearly a doubling in the prevalence of diabetes over 5 years in Scotland.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 10 publications
2
11
0
Order By: Relevance
“…Our finding that diabetes prevalence did not increase in continental western Europe (especially in northwestern Europe) is also consistent with reports from Sweden, 22 Germany, 23 and Switzerland 24 that covered a subset of our analysis years. Similarly, our estimated increases for high-income English-speaking countries are consistent with studies that had analysed repeated population-based surveys in the USA 25 and the UK 26, 27. A meta-analysis of 15 studies in Japan reported no increase in diabetes prevalence, 28 as observed in our analysis.…”
Section: Discussionsupporting
confidence: 91%
“…Our finding that diabetes prevalence did not increase in continental western Europe (especially in northwestern Europe) is also consistent with reports from Sweden, 22 Germany, 23 and Switzerland 24 that covered a subset of our analysis years. Similarly, our estimated increases for high-income English-speaking countries are consistent with studies that had analysed repeated population-based surveys in the USA 25 and the UK 26, 27. A meta-analysis of 15 studies in Japan reported no increase in diabetes prevalence, 28 as observed in our analysis.…”
Section: Discussionsupporting
confidence: 91%
“…Our reports are similar to the change in prevalence observed in the U.S. using National Health and Nutrition Examination Survey (NHANES) data, which showed an increase in prevalence of diabetes of 51% over the period of 1988–1994 to 2005–2006 (11). More recently, a study in Scotland showed an increase of 80% in diabetes prevalence over the period of 2003–2008 (12). …”
Section: Discussionmentioning
confidence: 99%
“…Thus, the DM prevalence almost doubled during the following five years, namely 5.2% in 2000 and 9.4% in 2008, respectively [23].…”
Section: Dm and Prediabetes Prevalence/ Incidence In Different Countrmentioning
confidence: 98%